(untitled) (Research, Society and Development, 2021)
Assess the risk of falls in the elderly and fundamental knowledge for the creation of public health care policies. The aim of this study was to investigate the use of the Timed Up and Go (TUG) test as a tool to assess the risk of falls in the elderly. This is a literature review of scientific articles indexed in the PubMed and Scielo databases, published between 2011 and 2021. Thus, the results obtained in the studies failed to demonstrate the efficiency of the TUG to assess the risk of falls in the elderly, in addition to the divergences analyzed, especially in relation to the cutoff score, as there are studies that point to different measures. Studies have failed to demonstrate the effectiveness of TUG in predicting falls in the elderly, but demonstrate its importance when used with other tests. There is a need for more studies on the subject, as they can contribute to clinical practice, guiding the best choice of tests to be applied to elderly people who are at risk of falls.